Do Earnings Subsidies Affect Job Choice? - Helen Connolly; Peter Gottschalk (Institute for the Study of Labor (IZA), 2004)
It is widely acknowledged that earnings subsidies promote employment by increasing rewards to labor market activity. This paper asks whether subsidies also affect job duration and wage growth. We provide an analytical framework that identifies causal links between earnings subsidies, job turnover, and wage growth. This framework highlights the importance of the form of the subsidy on the decision about the type of job to accept and, hence, its potential effect on within-job wage growth. The subsidy is predicted to increase job turnover and to affect between-job wage growth by affecting reservation wages. We use this framework to analyze the effects of the Canadian Self-Sufficiency Project (SSP). Consistent with the theory, we find that experimentals have shorter job duration and experience faster within-job and between-job wage growth than experimentals who continued to be eligible only for Income Assistance.
Keywords: J38; J23; 330; wage subsidy; job choice; Lohnsubvention; Arbeitsangebot; Arbeitsmobilität; Lohn; Schätzung; Vereinigte Staaten; EITC